Correlations between osteoartritis grading in femorotibial joint (kellgren lawrence) with cartilage defects grading - Permatasari, Yuliati; Zulqarnain, Nasirun; Sukmaningtyas, Hermina; Suntoko, Bantar (Indonesian Rheumatology Association, 2016)
Background : Osteoarthritis (OA) is the most common chronic rheumatic diseases that causing pain and disability. The imaging of knee OA were found in 15,5%Â men and 12,7% women of Indonesia population. Radiography is still used as a standard modalities in assesing OA progression, and Kellgren-Lawrence scale (KL) is the most common measurement used byclinicians. Superficial cartilage degradation is the first sign of OA, the early detection of the superficial cartilage degradation is very important for diagnosis. Our study was established to assess the correlation between OA grading in femorotibial joint examined by standard Kellgren-Lawrence scale (KL) measurement with cartilage defects examined by ultrasound.Methods : Observational analytic study with cross sectional and consecutive sampling was performed. Rank Spearman test for correlation of OA grading, cartilage defect, BMI and joint malalignment. McNemar test for correspondence between the location of the narrowing of the femorotibial joint and location of cartilage defects.Result : Correlation of OA grading of femorotibial joints (KL) with cartilage defects grading on ultrasound resulted r =0.459, p<0.05; correlation of OA grading of femorotibial joints (KL) with BMI or joint malalignment resulted p>0,05; correlation of cartilage defect grading with BMI or joint malalignment also resulted p>0.05. McNemar test for location of the narrowing of thefemorotibial joint with location of cartilage defects on ultrasound resulted p = 1.00, k = 0.714. There was a significant positive correlation of OA grading of femorotibial joints (KL) with cartilage defects grading on ultrasound. There was no significant correlation between OA grading of femorotibial joints (KL) with BMI and joint malignment, and no significant correlationbetween cartilage defects grading with BMI and joint malalignment. There is a correspondence between the location of the narrowing of the femorotibial joint with location of cartilage defects on ultrasound.Conclusion: For assesing the grade of osteoartritis, cartilage defect grading and assesment by ultrasound can be used as an alternative to X-Ray KellgrenLawrence scale (KL) measurement.Keywords : femorotibial joint, cartilage defects grading, osteoartritis grading examination, BMI, joint malalignment.